A framework for gender equality and social inclusion in agribusiness transformation in East and Southern Africa - Nortje, Karen; Joshi, Deepa; Enokenwa Baa, Ojongetakah; Mapedza, Everisto D.; Davis, Kristin E. (International Water Management Institute (IWMI), 2023)
A Gender Equality and Social Inclusion (GESI) approach is fundamental to agribusiness transformation in the Eastern and Southern Africa region. Work package 5 aims to bring about inclusive and scalable agribusiness innovations through targeted GESI support to UU ESA work packages 1-6. To achieve this, we produced this GESI framework on social, economic, political, and institutional barriers and opportunities to more inclusive agribusiness in the ESA region. This framework will ensure that planned interventions under UU are designed and implemented to empower more women and youth as farmers, agribusiness owners, and actors with voice and visibility across agribusiness value chains. The GESI framework was produced by reviewing relevant literature and talking to agribusiness stakeholders, especially women and youth, in four initial countries: Ethiopia, Kenya, Zambia, and Zimbabwe.